2021
DOI: 10.20961/ssej.v1i3.56071
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Kecemasan Terhadap Kualitas Tidur Ibu Hamil Trimester III Di Puskesmas Tanjung Karang Mataram

Abstract: <p><strong>Pendahuluan: </strong>Kecemasan merupakan keadaan patologis yang ditandai dengan gejala fisiologis dan gejala psikologis, gejala-gejala tersebut dapat terjadi berbeda pada setiap orang dan situasi. Pada kehamilan, risiko terjadinya kecemasan akan meningkat. Memasuki trimester tiga, ibu hamil dapat merasa cemas akan keselamatan dirinya maupun keselamatan bayinya. Saat merasa cemas, akan terjadi peningkatan kadar noradrenergik akibat stimulasi sistem saraf simpatis yang akan menyebab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Sleep significantly contributes to the restoration or renewal of mental and physiological power and is required for doing new tasks and responsibilities. 4 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep significantly contributes to the restoration or renewal of mental and physiological power and is required for doing new tasks and responsibilities. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Sleep significantly contributes to the restoration or renewal of mental and physiological power and is required for doing new tasks and responsibilities. 4 Sleep is essential for the normal growth and development of both mind and body. A good sleep pattern is important for a healthy pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also showed a strong and positive relationship between anxiety levels and sleep quality in third trimester pregnant women [10,11]. Meanwhile, the results of other studies showed there was no relationship between anxiety in facing childbirth and sleep quality of third trimester pregnant women [12]. There was no significant association between gestational anxiety and poor sleep quality [13].…”
Section: Introductionmentioning
confidence: 97%